Metallothioneins failed to reflect mercury external levels of exposure and bioaccumulation in marine fish - Considerations on tissue and species specific responses - Mieiro, C. L.
The suitability of metallothioneins (MT) in fish as biomarker of exposure to mercury has been questioned. Therefore, this study aimed at investigating the relationship between external levels of exposure, mercury accumulation and MT content, assessing species and tissue specificities. Two ecologically different fish species – Dicentrarchus labrax and Liza aurata – were surveyed in an estuary historically affected by mercury discharges. Total mercury (T-Hg) and MT content were determined in gills, blood, liver, kidney, muscle and brain. All tissues reflected differences in T-Hg accumulation in both species, although D. labrax accumulated higher levels. Regarding MT, D. labrax revealed a depletion in brain MT content and an incapacity to induce MT synthesis in all the other tissues, whereas L. aurata showed the ability to increase MT in liver and muscle. Tissue-specificities were exhibited in the MT inducing potential and in the susceptibility to MT decrease. L. aurata results presented muscle as the most responsive tissue. None of the investigated tissues displayed significant correlations between T-Hg and MT levels. Overall, the applicability of MT content in fish tissues as biomarker of exposure to mercury was uncertain, reporting limitations in reflecting the metal exposure levels and the subsequent accumulation extent.